Nest-Site Selection by Slender-Billed Parakeets in a Chilean Agricultural-Forest Mosaic - Vergara-Egert, P (WILEY-BLACKWELL, 2013)
Species in the family Psittacidae may be particularly vulnerable to anthropogenic habitat transformations that reduce availability of suitable breeding sites at different spatial scales. In southern Chile, loss of native forest cover due to agricultural conversion may impact populations of Slender-billed Parakeets (Enicognathus leptorhynchus), endemic secondary cavity-nesting psittacids. Our objective was to assess nest-site selection by Slender-billed Parakeets in an agricultural-forest mosaic of southern Chile at two spatial scales: nest trees and the habitat surrounding those trees. During the 20082009 breeding seasons, we identified nest sites (N= 31) by observing parakeet behavior and using information provided by local residents. Most (29/31) nests were in mature Nothofagus obliqua trees. By comparing trees used for nesting with randomly selected, unused trees, we found that the probability of a tree being selected as a nest site was positively related to the number of cavity entrances, less dead crown, and more basal injuries (e.g., fire scars). At the nesting-habitat scale, nest site selection was positively associated with the extent of basal injuries and number of cavity entrances in trees within 50 m of nest trees. These variables are likely important because they allow nesting parakeets to minimize cavity search times in potential nesting areas, thereby reducing energetic demands and potential exposure to predators. Slender-billed Parakeets may thus use a hierarchical process to select nest sites; after a habitat patch is chosen, parakeets may then inspect individual trees in search of a suitable nest site. Effective strategies to ensure persistence of Slender-billed Parakeets in agricultural-forest mosaics should include preservation of both individual and groups of scattered mature trees. RESUMEN Especies de la familia Psittacidae pueden ser particularmente vulnerables a transformaciones antropogenicas del habitat, lo cual reduce la disponibilidad de lugares adecuados para reproducirse a diferentes escalas espaciales. En el sur de Chile, la perdida de cobertura boscosa debido a la conversion agricola puede afectar las poblaciones de Enicognathus leptorhynchus, un psittacido endemico que anida en cavidades existentes (anidador secundario en cavidades). Nuestro objetivo fue evaluar la seleccion de lugares de anidacion por Enicognathus leptorhynchus en un mosaico de agricultura y bosque en el sur de Chile en dos escalas espaciales: arboles para anidar y el habitat que rodea ha estos arboles. Durante la temporada reproductiva del 20082009, identificamos lugares de anidacion (N= 31) mediante la observacion del comportamiento del perico e informacion proporcionada por los residentes locales. La mayoria de los nidos (29/31) se localizaron en arboles maduros de Nothofagus obliqua. Mediante la comparacion de arboles usados para anidar con arboles seleccionados de manera aleatoria, encontramos que la probabilidad de que un arbol sea seleccionado como un lugar de anidacion se relaciono positivamente con el numero de entradas a la cavidad, menor numero de copas muertas, y mas heridas basales (e.g., cicatrices por fuegos). A la escala de anidacion de habita, la seleccion de lugares de anidacion se asocio positivamente con el grado de heridas basales y numero de entradas a la cavidad en arboles localizados a menos de 50 m del arbol donde estaba el nido. Estas variables probablemente son importantes porque permiten que los pericos que estan anidando minimicen el tiempo de busqueda de cavidades en potenciales areas de anidacion, de este modo reduciendo las demandas energeticas y la exposicion potencial a depredadores. El perico (E. leptorhynchus) puede asi usar un procesos jerarquico de seleccion de lugares de anidacion; despues que un parche de habitat es elegido, los pericos pueden entonces inspeccionar arboles de manera individual en busqueda de lugares adecuados para anidar. Estrategias efectivas para asegurar la persistencia del perico (E. leptorhynchus) en mosaicos de agricultura y bosque deberian incluir la preservacion tanto de individuos como de grupos de arboles maduros dispersos.